Genetically-enriched microbe-facilitated self-healing concrete – a sustainable material for a new generation of construction technology. Issue 127 (14th December 2015) - Sarkar, Manas; Adak, Dibyendu; Tamang, Abiral; Chattopadhyay, Brajadulal; Mandal, Saroj
Abstract : Genetically modified spore forming B. subtilis bacterial cells for eco-friendly sustainable self-healing bio-concrete. Abstract : The fundamentals of engineering and structural properties such as mechanical strength, durability, bond strength, and self-healing behaviour of a genetically-enriched microbe-incorporated construction material have been explored in the present study. The alkaliphilic Bacillus subtilis bacterium is able to survive inside the concrete/mortar matrices for an extended period due to its spore forming ability. The bioremediase-like gene of a thermophilic anaerobic bacterium BKH2 (GenBank accession no. KP231522) was thus transferred to the bacillus strain to develop a true self-healing biological agent. Incorporation of the transformed bacterial cells at different concentrations in the bio-concrete/mortar exhibited higher mechanical strengths and improved durability of the samples in comparison to the normal cement–sand mortar/concretes. Microstructural analyses confirmed the formation of a novel gehlenite (Ca2 Al2 SiO7 ) phase besides calcite deposition inside the matrices of the transformed Bacillus subtilis -amended cementitious materials. The gradual development of nano rod-shaped gehlenite composite within the bio-mortar matrices was due to the biochemical activity of the bioremediase-like protein expressed within the incorporated bacterial cells. This development significantly increased the true self-healing property as well as enhanced the mechanical strength of the bio-concrete/mortar material which was sustained for a prolonged period. This study demonstrates a new approach towards the enhancement of structural properties and true self-healing activity by genetically-enriched spore-forming Bacillus sp. with advancement towards sustainable and green construction technology.